A Smart Polymeric Sol‐Binder for Building Healthy Active‐Material Microenvironment in High‐Energy‐Density Electrodes (Adv. Energy Mater. 6/2023). Issue 6 (11th February 2023) - He, Yan; Jing, Lei; Feng, Lanxiang; Yang, Sifan; Yang, Jiarui; Fu, Xuewei; Yang, Wei; Wang, Yu
Abstract : Active Material Microenvironment Similar to the cell microenvironment, the active‐material microenvironment (ME@AM) in battery electrodes fundamentally controls the electrochemical reactions of individual active‐material particles. In article number 2203272, Xuewei Fu, Wei Yang, Yu Wang and co‐workers report a "smart" high‐performance polymeric sol‐binder to build "healthy" ME@AM. The new concept and findings may reshape the understanding of electrode microstructures and the roles of binders.